Complexidade, competitividade e desenvolvimento das capacidades produtivas do Brasil pós-abertura comercial da década de 1990 - Vilarinho, Rafael Bastos (2018)
This work is to analyze the Brazilian commercial insertion according to the economic complexity of exported products post-trade openness of the decade of 1990. The work has an objective to analyze the agenda of brazilian exports from the process of openness of the economy at the beginning of the 1990s and check if this process was really capable of making international trade a favorable environment to structural change. The analysis will be used for the approach of economic complexity, as well as the structuralist approach and Neo-Schumpeterian, defines the productive structure of a country the fundamental basis for the process of economic development. The complexity cost analyzes the exports of certain economy, highlighting whether or not there is a sophistication of goods produced and exported by an economy. The method believes that countries exporting goods sophisticated feature a productive structure for this, and for this reason through insertion in international trade it is possible to infer about the productive structure of the economy. The importance stems precisely from the analysis of international trade have a vision of productive capacities, after all economically developed countries are those that have a diversified export tariff and based on complex products with high technological content. Exports of a country reveal not only their status quo in world trade, but also reflect its productive structure and autonomy regarding the technological progress. In the Brazilian case the difficulty to specialize in the production of goods sophisticated follows the limits that its productive structure, heterogeneous character with high competitiveness in the export of primary, prints in innovative processes. The process of opening up of the economy was not capable of modifying the structure of the economy enough so that the United States entered into a trajectory of economic development driven by trade, based on more sophisticated products.